Islamic Radicalism: History and a Case Study in the Indonesia Context - Putrawan, Bobby Kurnia; Eunike, Pratiwi (Jurnal Theologia, 2021)
In the history of Islam, in the classical era, radicalism has existed, so it is not a new phenomenon in the modern age. Since the time of the Caliph Umar radicalism has emerged, but not yet organized, only in the time of the Caliph Ali bin Abu Talib this movement began to be systemized and organized through a Khawarij theological movement with its radical and uncompromising understanding of various acts of violence to oppose the tahkim or arbitration between the caliphs. Ali ibn Abi Talib and Muawiyah. Arbitration takes place in the context of the Shiffin war in which the khawarij group considers those who agreed to deviate from Islamic teachings. Later in Cairo an organization that had the same characteristics as the khawarij emerged, who wanted the authenticity of the teachings of Islam in the form of literal interpretation, without compromise, softening or reduction or reinterpretation. In filling out theological studies related to radicalism, this research was made to analyze "The relationship between radical genealogists in the classical period and the contemporary era in interpreting the Qur'an literally" At the end of the analysis will discuss the deconstruction of jihad as an effort to explain the meaning of jihad from various paradigms.